Literature review and case study: unveiling the complexities of mandibular second molar with three distal canals - Anoushka Yadav; Anushka Arora; Karthik Shetty; Mohmed Isaqali Karobari (BMC, 2024)
Abstract The occurrence of morphological deviations in root canal anatomy is challenging and can influence treatment outcomes. While mandibular second molars typically have 2 roots and 3 canals, a unique case emerged in a 23-year-old Indian male with a symptomatic permanent left mandibular second molar showing three distal, two mesial canals, and two roots. The tooth presented as non-mobile but tender on percussion. The patient was diagnosed with symptomatic irreversible pulpitis with symptomatic apical periodontitis. The presence of mid distal canal was radiographically and visually confirmed with the aid of limited FOV cone-beam computed tomography and the dental operating microscope. Successful nonsurgical root canal treatment with 6-month follow-up has been documented in this case report.